Utilization of Coal Combustion Waste (Fly Ash) For Geopolymer Concrete as Green Concrete - Arie Putranto, Nugroho (Green Publisher, 2022)
The use of Portland Cement as a paste in conventional concrete is still often the primary/favourite choice in civil engineering construction. In time, cement production will cause harm to the environment, especially in the production process, and the availability of natural raw materials in cement production will dwindle. Therefore, it is necessary to find an innovative alternative to replace cement utilization. From the test matrix that has been carried out, it can be concluded that the waste from burning coal (fly ash), can be used as a substitute for Portland cement, and also at the composition of 16 moles – the ratio of sodium silicate to sodium hydroxide of 1.5 has a strong quality much better compression than the composition when using a 100% Portland cement mixtureFrom the test matrix that has been carried out, it can be concluded that the waste from burning coal (fly ash), can be used as a substitute for Portland cement, and also at the composition of 16 moles – the ratio of sodium silicate to sodium hydroxide of 1.5 has a strong quality. much better compression than the composition when using a 100% Portland cement mixture.